2002
DOI: 10.1002/1522-2675(200210)85:10<3078::aid-hlca3078>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

New Asymmetric Catalysis by (Salen)cobalt(III) Complexes (Salen=[Bis(salicylidene)ethylenediaminato]={{2,2′-[ethane-1,2-diyl]bis[(nitrilo-N)methylidyne]bis[phenolato-O]}(2−)}) of cis--Structure: Enantioselective Baeyer-Villiger Oxidation of Prochiral Cyclobutanones

Abstract: New Asymmetric Catalysis by (Salen)cobalt(III) Complexes (Salen [Bis(salicylidene)ethylenediaminato] {{2,2'-[ethane-1,2-diyl]bis[(nitrilo-kN)methylidyne]bis[phenolato-kO]}(2 À)}) of cis-b-Structure: This paper is dedicated with admiration and respect to Professor Dieter Seebach on the occasion of his sixty-fifth birthday A series of chiral (salen)cobalt(III) complexes (salen [bis(salicylidene)ethylenediaminato] {{2,2'-of cis-b structure were prepared and used for the enantioselective Baeyer-Villiger oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…The reaction was quenched by addition of an aqueous solution of Na 2 SO 3 (0.1 mL), and the product 5 was purified by column chromatography on silica gel (petroleum ether/ethyl acetate, 6:1) in 99 % yield. [ α ] D 20 = –66.5 ( c 0.71, CHCl 3 ), 95 % ee [ref 10c. [ α ] D 20 = +62 ( c 1.0, CHCl 3 ) for (1 R ,4 S ,7 S ,10 R )‐isomer with >98 % ee ].…”
Section: Methodsmentioning
confidence: 99%
“…The reaction was quenched by addition of an aqueous solution of Na 2 SO 3 (0.1 mL), and the product 5 was purified by column chromatography on silica gel (petroleum ether/ethyl acetate, 6:1) in 99 % yield. [ α ] D 20 = –66.5 ( c 0.71, CHCl 3 ), 95 % ee [ref 10c. [ α ] D 20 = +62 ( c 1.0, CHCl 3 ) for (1 R ,4 S ,7 S ,10 R )‐isomer with >98 % ee ].…”
Section: Methodsmentioning
confidence: 99%
“…Uchida and Katsuki showed that cobalt salen complexes of the type 166 (5 mol %) mediated the oxidation of 3-phenyl-substituted cyclobutanone with H 2 O 2 and UHP, demonstrating good yields (72–92%) and moderate to good enantioselectivities (50–77% ee). , Ethanol was identified as the preferred reaction solvent, and UHP was shown to afford chiral lactones with higher optical yields than H 2 O 2 . Strukul and co-workers conducted the oxidation of cyclobutanones with H 2 O 2 in water in the presence of cobalt salen complex 167 (1 mol %); for the solubilization of the hydrophobic substrate and catalyst, micelles were used .…”
Section: Asymmetric Baeyer–villiger Oxidationsmentioning
confidence: 99%
“…In recent years, the inexpensive, commercially available, and environmentally friendly H 2 O 2 was utilized in the Baeyer–Villiger reaction with increasing frequency. Various catalysts that activate hydrogen peroxide, such as heterogeneous catalysts based on solid acids [ 201 ], zeolites [ 202 – 203 ], Se [ 204 ], As [ 205 ], Co [ 206 ], sulfonated organic ion exchange resins [ 203 , 207 ], and homogeneous catalysts based on Pt [ 208 ], Zr [ 209 ], Re [ 210 – 211 ], Se [ 212 213 ], As [ 205 ], Mo [ 214 ], Co [ 215 ], Brønsted [ 216 ], and Lewis acids [ 217 ] are described in the literature. The general mechanism of a Lewis acid-catalyzed Baeyer–Villiger rearrangement is presented in Scheme 3 [ 200 , 218 ].…”
Section: Reviewmentioning
confidence: 99%